Channel Estimation for MIMO OFDM Systems using LS and MMSE Channel Estimation Techniques - R. Jeya, B.Amutha, Roshni Patra, Rishav Ghosh (International Journal of Advanced Science and Technology, 2020)
Multiple Input Multiple Output, also known as MIMO, is a very useful technology that can be used to meet the increasing demand for wireless communications and to achieve transmission speed and data. Various channel estimation techniques can be used to predict the transmission and reception of data between antennas. In this paper, the LS (least squares) and MMSE (Minimum Mean Square Error) estimation method is used, which yield good results.